Efektivitas Tanaman Bintaro (Cerbera manghas) dalam Menekan Serangan Penyakit Moler pada Bawang Merah (Allium ascalonicum L.) di Lahan Gambut - Dayatullah, Dayatullah; Salamiah, Salamiah; Aidawati, Noor (www.ulm.ac.id, 2024)
Shallots are one of the important vegetable commodities that have been intensively cultivated by farmers for a long time, including in the non-substituted spices group which functions as food flavoring seasonings and ingredients for traditional medicine. In the production process, various constraint were found, one of which is the attack of pathogens that cause moler disease. This study aims to determine the effectiveness of Bintaro solution on the intensity of Moler disease attacks on shallot plants on peatlands. The study was conducted at the Phytopathology Laboratory, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru and in Tegal Arum Village, Landasan Ulin District, Banjarbaru City, South Kalimantan, from June to October 2022. The study used a completely randomized design consisting of 4 treatments and 5 replications. The treatment tested was the application of old b intaro fruit, young bintaro fruit, bintaro leaves plus 1 control treatment. The application of vegetable pesticides was carried out by pouring the solution onto the surface of each shallot plant as much as 5 ml per plant, which was carried out 7 times with an interval of 1 week. Parameters observed were the intensity of the attack of moler disease, fresh weight of the bulbs, the number of bulbs and the diameter of the shallot bulbs. The results showed that the incubation period for the pathogen causing moler disease was 14 days. The application of bintaro plant solution was unable to suppress the attack of moler disease on shallots on peatlands and was unable to increase the number of shallot bulbs, but the application of old bintaro fruit was able to increase tuber wet weight by 41kg/ha and tuber diameter by 2%.